The role of herpesvirus 6A and 6B in multiple sclerosis and epilepsy. (23rd October 2020) - Dunn, Nicky; Kharlamova, Nastya; Fogdell‐Hahn, Anna
Abstract: Human herpesvirus 6A (HHV‐6A) and 6B (HHV‐6B) are two closely related viruses that can infect cells of the central nervous system (CNS). The similarities between these viruses have made it difficult to separate them on serological level. The broad term HHV‐6 remains when referring to studies where the two species were not distinguished, and as such, the seroprevalence is over 90% in the adult population. HHV‐6B has been detected in up to 100% of infants with the primary infection roseola infantum, but less is known about the primary infection of HHV‐6A. Both viruses are neurotropic and have capacity to establish lifelong latency in cells of the central nervous system, with potential to reactivate and cause complications later in life. HHV‐6A infection has been associated with an increased risk of multiple sclerosis (MS), whereas HHV‐6B is indicated to be involved in pathogenesis of epilepsy. These two associations show how neurological diseases might be caused by viral infections, but as suggested here, through completely different molecular mechanisms, in an autoimmune disease, such as MS, by triggering an overreaction of the immune system and in epilepsy by hampering internal cellular functions when the immune system fails to eliminate the virus. Understanding the viral mechanisms of primary infection and reactivation and their spectrum of associated symptoms will aid our ability to diagnose, treat and prevent these severe and chronic diseases. This review explores the role of HHV‐6A and HHV‐6B specifically in MS and epilepsy, the evidence to date and the future directions of this field.